2010
DOI: 10.19030/iber.v9i8.620
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of Education On Economic Growth: The Case Of Mauritius

Abstract: This paper focuses on the impact of investment in education on economic growth in Mauritius. It is an attempt to explore the extent to which education level of the Mauritian labour force affects its economic growth that is its output level. We have used the Cobb-Douglas production function with constant returns to scale where human capital is treated as an independent factor of production in the human capital augmented growth model. We expect to contribute to the existing literature by bringing evidence from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 29 publications
1
39
0
2
Order By: Relevance
“…The central theoretical research on the interconnection of the human capital and growth can be sum up in the following: (i) the human capital intensifies growth (Lucas, 1988); (ii) economic growth rest on the prevailing human capital generating new knowledge (Mankiw, Romer & Weil, 1992); (iii) the human capital promotes the copying or adaptation of new or innovative technologies (Nelson & Phelps, 1966); (iv) the human capital is correlated with the amount of stock accumulated (Azariadis & Drazen, 1990). For several decades, the effects of human capital on economic growth has been a topic of research both from the macroeconomic perspective (see Pereira and Aubyn, 2004;Odit, Dookhan, & Fauzel, 2010) among many others, and from the micro perspective (Psacharopoulos, 1995;Bouaissa, 2009) to name but a few. Mankiw et al, (1992) showed that human capital impacts economic growth positively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The central theoretical research on the interconnection of the human capital and growth can be sum up in the following: (i) the human capital intensifies growth (Lucas, 1988); (ii) economic growth rest on the prevailing human capital generating new knowledge (Mankiw, Romer & Weil, 1992); (iii) the human capital promotes the copying or adaptation of new or innovative technologies (Nelson & Phelps, 1966); (iv) the human capital is correlated with the amount of stock accumulated (Azariadis & Drazen, 1990). For several decades, the effects of human capital on economic growth has been a topic of research both from the macroeconomic perspective (see Pereira and Aubyn, 2004;Odit, Dookhan, & Fauzel, 2010) among many others, and from the micro perspective (Psacharopoulos, 1995;Bouaissa, 2009) to name but a few. Mankiw et al, (1992) showed that human capital impacts economic growth positively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, Dauda (2010), using OLS, finds a positive effect of total education expenditure on GDP growth. By estimating an Error Correction Model via the "one step" procedure, Odit et al (2010) report a positive effect of schooling years on GDP per-worker growth, while Nurudeen and Usman (2010) via least squares reveal that expenditure on education has a negative effect on GDP growth. Finally, Lawal and Iyiola (2011) conclude that primary enrollment and total expenditure on education have a negative impact on growth, whereas capital, recurrent education expenditure, gross capital formation, post-primary and tertiary education enrollment affect growth positively using OLS.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The result implied that education per worker in Indonesia had a significant positive impact on economic growth of the country. Odit et al (2010) investigated the impact of investment in education on economic growth of Mauritius using Cobb-Douglas Production function. The study covered a period from 1990 to 2006 and the findings revealed that human capital impacted positively and significantly on economic growth.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Education is a method by which the basic information and knowledge are obtained through the means of tutoring and book studying. Education provides access to skills and knowledge necessary to adapt an economy to new technologies that boost economic growth (Odit, Dookhan & Fauzel, 2010). The expenses on training can produce superior workforce which can efficiently and economically put modern technology into use in any form of production process (Mallick, Das & Pradhan, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation